Критерії аудиторської оцінки фінансової звітності - Фальченко, Олена Олександрівна; Лозенко, Олена Андріївна (My University, 2019)
У статті систематизовано визначення поняття «критерії». Обґрунтовано необхідність використання критеріїв оцінки під час аудиту фінансової звітності. Визначено концептуальну основу фінансової звітності загального призначення для підприємства, які використовують національні стандарти бухгалтерського обліку для складання фінансової звітності. Досліджено та виділено основні чинники, що впливають на вибір критеріїв аудиторської оцінки фінансової звітності. Проаналізовано існуючі критерії аудиторської оцінки фінансової звітності, і запропоновано базовий перелік на підставі стандартів обліку та аудиту. Обґрунтовано необхідність використання концептуальної основи фінансової звітності загального або спеціального призначення для визначення оптимального набору якісних характеристик фінансової звітності для її оцінки за критеріями. Встановлено, що доречність застосування будь-якого критерія або їх сукупності залежить від конкретних обставин на підприємстві, у тому числі ідентифікованих аудитором ризиків, пов'язаних з утвердженням, а також ефективності різних критеріїв. Результати дослідження показали необхідність розроблення методики, яка дасть змогу визначити ефективні критерії аудиторської оцінки фінансової звітності.

Generally known, that an audit shows by itself the independent audit of financial records and utterance of idea in relation to her. By a basic problem in achievement of this aim of audit, id est estimations of the financial reporting are decision of question, as well as on what exactly main or substantial to send work of public accountant. Today, a significant amount of information that is used in assessing the results of an enterprise can be obtained from financial statements. But if the financial statements have significant distortions and do not contain financial results, then the management decisions made may lead to incorrect conclusions about the results of operations and to the use of ineffective actions to increase their effectiveness. The article gives the definition of “criteria”. It is given the necessity of using the evaluation criteria in an audit of financial statements. A conceptual framework for general purpose financial reporting has been defined for entities that use national accounting standards to prepare financial statements. The main factors influencing the selection of criteria for the audit assessment of financial statements are investigated and highlighted. The existing criteria for the audit assessment of financial statements are analyzed, and a basic list is proposed based on accounting and audit standards. The necessity of using the conceptual framework of general or special purpose financial statements to justify the optimal set of qualitative characteristics of financial statements for its assessment by criteria is substantiated. It was established that the appropriateness of applying any criterion or their combination depends on the specific circumstances of the enterprise, including the risks identified by the auditor associated with the approval, as well as the effectiveness of various criteria. The choice of the list of evaluation criteria depends on the level of application: at the level of financial statements as a whole, and at the level of approval. The results of the study showed the need to develop a methodology that will determine the effective criteria for the audit assessment of financial statements.
Criteria of audit evaluation in financial reporting
Keywords: аудит; фінансова звітність; оцінка; критерії; бухгалтерський облік; audit; financial reporting; assessment; criteria; accounting